ASSOCIATION OF PLASMA LEPTIN WITH CORONARY ARTERY CALCIUM (CAC) IN ADULTS: Plasma Leptin And Coronary Artery Calcium - Khan, Dr Aysha Habib; Imran, Sheharbano; Hussain, Zainab; Jafri, Lena; Majid, Hafsa; Sajjad, Zaffar (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the correlation between leptin and CAC in scores subjects without cardiovascular disease (CVD) risk. Study Design: Cross sectional study. Place and Duration of Study: Aga Khan University Hospital, from Mar 2014 to Jun 2015. Material and Methods: Total 128 subjects were included. The study was approved by ethical review committee. After informed consent a predesigned questionnaire was documented. Subjects without known cardiac disease history, coming for non-contrast CT scan for abdominal indications were included. Leptin levels were measured by Enzyme immunoassay. CAC scores were assessed on a 64 slice non-contrast CT scan. Data analyzed by SPSS version 20. Results: Total 128 subjects were included with mean age 42.82 ± 13.1 years and 78.1% (n=100) were males. Mean BMI and waist circumference was 27.1 ± 5.4 kg/m2 and 94.8 ± 9.0cm respectively. High median leptin levels were seen in 11.7% (n=15) of study subjects. Leptin levels were also significantly higher in female compared to male [12.5ng/ml (0.3-60.9) vs. 2.5ng/ml (0.1-50); p-value=0.001]. High CAC score was present in 15% (n=19) of study subjects. Statistically significant correlation of leptin was found with waist circumference, (r 0.50; p=0.001), positive correlation with BMI (r 0.51, p<0.05) with higher levels noted in obese subjects compared to overweight and normal BMI subjects [median 7.5ng/ml (0.3-60.9) vs. 3.3ng/ml (0.1-40) & 0.1 ng/ml (0.1-0.1)]; No correlation was found between CAC score and serum leptin levels (r 0.073; p=0.41). Conclusions: Leptin levels are not correlated with CAC scores in subjects with low CVD risk. However, leptin was significantly higher in females and subjects with increased waist circumference.